TINGKAT CUSTOMER LOYALITY BERBASIS ISLAMIC BUISNESS ETHIC DAN BRAND IMAGE - Nerdin,SE -; Dra. Alifah Ratnawati.,SE.,MM - (Conference In Business, Accounting, And Management (CBAM), 2015)
Intense competition in the service industry make service companies to intervene and work hard for the survival of the company 'why do not companies must not only create a good product and quality but the company is also required as to how the company could create good ethics and brand image to consumers. ethics or corporate brand image can not be replicated or followed as ethics and good brand image will be embedded in the minds of consumers so as to enable the consumer to use the product in a sustainable manner so as to make consumers become satisfied and loyal. The analysis technique used in this study uses the concept Equatin Structural Model (SEM) with a program Partial Least Square (PLS).Â  Â Keywords: Islamic buisness ethic, business ethic, brand image, customer satisfaction, customer loyality.